PENGARUH KUALITAS PRODUK TERHADAP BRAND IMAGE PRODUK ROTI BREADTALK DI JAKARTA - Handayani, Fitrie; Bawono, Adhi; Viktor, Viktor (Jurnal Pengabdian dan Kewirausahaan, 2020)
The culinary industry is an industry that is always developing. One area of business that is currently starting to develop is bakery products The purpose of this research is (1) To know the effect of product quality toward brand image of Bread Talk as bakery shop that use open kitchen concept. The method used in this study is a quantitative research method. Populations and samples (questionnaires) in this study were 85 valid questionnaires. Data analysis was performed by testing the validity, reliability, normality test, correlation coefficient test, determination test, linear regression and T test. The results of this study indicate that the product quality variable and brand image variable have a strong relationship with a correlation value of 0.777 and the product quality variable has a significant effect on the brand image variable with t count of the product quality is 11.237 with a significant value of product quality is 0.000. The calculation results of the product quality variable influece on the brand iamge variable is 60.3% and the remaining 39.7% is influenced by other variables outside of the study. Thus, BreadTalk should be able to continue to maintain and improve the quality of its products in order to maintain the achievements of its brand image Keywords: Product Quality, Brand Image, Branding